2012
DOI: 10.1136/bcr-2012-006759
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypertrophic osteoarthropathy in the case of pulmonary metastasis secondary-to-nasopharyngeal carcinoma with zoledronic acid: an enlightening experience

Abstract: SummaryWe describe a case of 23-year-old man, who presented with painful hypertrophic pulmonary osteoarthropathy involving bilateral upper and lower extremities, resulting from intrathoracic metastasis. The patient had a history of undifferentiated nasopharyngeal carcinoma which was treated successfully 2 years ago. The painful osteoarthropathy had made the patient incapacitated. A single dose of 4 mg of intravenous zoledronic acid (ZA) was given which resulted in complete resolution of pain along with reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
2
0
3
Order By: Relevance
“…По данным некоторых исследований, терапия бисфосфонатами (золедроновой кислотой, памидроновой кислотой) может быть эффективна как при первичной, так и при вторичной гипертрофической остеоартропатии [24][25][26]. Помимо ингибирования резорбции костной ткани остеокластами бисфосфонаты обладают противовоспалительным действием, а также снижают уровень фактора роста эндотелия сосудов [27].…”
Section: Discussionunclassified
“…По данным некоторых исследований, терапия бисфосфонатами (золедроновой кислотой, памидроновой кислотой) может быть эффективна как при первичной, так и при вторичной гипертрофической остеоартропатии [24][25][26]. Помимо ингибирования резорбции костной ткани остеокластами бисфосфонаты обладают противовоспалительным действием, а также снижают уровень фактора роста эндотелия сосудов [27].…”
Section: Discussionunclassified
“…However, patients respond differently, and sometimes total relief is not achieved and the intense arthralgia subsists. In cases where pain is refractory to conventional analgesia, case studies have reported success with bisphosphonates including zoledronic acid and pamidronate [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Terapia farmakologiczna na ogół obejmuje konwencjonalne zastosowanie NSAID, opioidów i glikokortykoidów, jednak skuteczność przeciwbólowa powyższych metod w przypadku bólu stawowego towarzyszącego HOA jest zmienna. W przypadkach występowania bólu opornego na konwencjonalną analgezję, przeprowadzone analizy dowiodły skuteczności stosowania bisfosfonianów, w tym kwasu zolendronowego i pamidronatu [7][8][9].…”
Section: Dyskusjaunclassified
“…A variety of diseases, including cyanotic heart disease [3], pulmonary metastasis, and notably lung cancer [4], have been recognized as etiologies of the secondary form. Liver cirrhosis has been identified as a culprit in other cases as well [5].…”
Section: Discussionmentioning
confidence: 99%